INOVASI PEMBELAJARAN BERBASIS IMMERSIVE DAN VIRTUAL REALITY PADA KOMUNIKASI PEMULA BAHASA ARAB - Azisi; Priyono, Dwi Juli; Nurfaiza (Institut Kariman Wirayudha Sumenep, 2025)
Learning Arabic for beginners often faces challenges in creating an engaging and effective learning experience. Immersive technology and virtual reality (VR) offer innovative solutions to improve communication skills in Arabic. This study uses quantitative and qualitative approaches to evaluate the impact of using VR technology in Arabic language learning. Data was collected through written tests, observations, and interviews with students involved in VR-based learning programmes. The analysis was carried out to assess the improvement of students' communication skills and learning motivation. The findings show that the use of VR technology significantly improves students' communication skills in Arabic. Students reported increased motivation and engagement in the learning process, as well as better speaking skills in everyday communication situations. In addition, the interactive and realistic learning experience helps students feel more confident in using Arabic. While there are many benefits, the study also identifies challenges related to technology accessibility and the need for adequate infrastructure.Teachers' involvement in the planning and implementation of VR technology is essential to ensure learning effectiveness. The application of immersive technology and VR in learning Arabic for beginners has great potential to improve students' communication skills. Recommendations for educational institutions include the adoption of these technologies in the curriculum, training for teachers, and attention to the necessary infrastructure. This research is expected to be a reference for the development of more innovative and effective learning methods in the future